Comparison of Financial Performance Buku III Indonesian Banks Using Risk-Based Bank Rating (RBBR) Method: Case Study of PT. Pan Indonesia Bank, Tbk (Panin) and PT. Bank Mega, Tbk (Mega) - Wiwiek Mardawiyah Daryanto (Sekolah Tinggi Manajemen IPMI, 2020)
Indonesia has experienced economic crisis in 1997/1998 and 2008, these events motivate the government to have a strong assessment to evaluate the financial health of the company. Related to the banks industry, government of Indonesia through Financial Service Authority or Otoritas Jasa Keuangan (OJK) issued the Circular Letter of OJK No. 14/SEOJK.03/2017 about Risk-Based Bank Rating (RBBR) approach that include the evaluation of risk profile, good corporate governance, earnings, and capital. The purpose of this study is to assess the financial health of the two open recorded non-expressed claimed BUKU III banks in Indonesia, which are Bank PT. Pan Indonesia Bank, Tbk (Panin) and PT. Bank Mega, Tbk (Mega) from year of 2014 to 2018. The methodology used is RBBR approach concerning the Rating of Health of Commercial Banks. The data were collected from the yearly report of the banks, fiscal reports, diaries, and articles of PT. Bank Mega and PT. Bank Panin. During the five year trend, the result of this study reveals that the two banks have performed well. However, Bank Mega has performed better in terms of Loan to Deposit Ratio (LDR) compared to Bank Panin. This study has added the knowledge in the financial literature. It also brings benefit for managers to help them make a better decision to address their company’s problem.